Compost Treatment for a Sustainable Growth in Natural Grassland in Hungary - Daniel Díaz Fernández; István Csízi; Géza Nagy (Scientific Papers Animal Science and Biotechnologies, 2023)
Grassland ecosystems can be found on every continent, except Antarctica thanks to their high tolerance and adaptability. Moreover the grassland based animal husbandry is an ancient and easy way for food production even in regions where other agricultural sectors cannot be effective. On the other hand these ecosystems are not only valuable because of their role in food production. Grasslands take their share in carbon sequestration, erosion controlling and the conservation of biodiversity and that is why the European Union made strict rules about grassland management. In our experiment we tested two different types of compost - what are officially allowed in organic farming - on natural grassland in Hungary. Three rates of compost (10 t/ha, 20 t/ha, 30 t/ha) were tested on 3m X 10m experimental plots in four replication. Both type had four control plots too, this way we had 32 experimental plots. We measured the botanical composition in May and September, what was followed by harvesting and the measurement of the yield. Samples for laboratory analysis were also taken. Dry matter yield of the pasture showed positive responses to the rates of compost but the protein yield per unit area only grows until a certain point and then it drops down. Our results indicate that the application of these composts is a sustainable method of increasing the productivity of natural grasslands.